The Influence of Emotional Intelligence on Life Satisfaction in Adolescence - Lorea Azpiazu; Arantzazu Rodríguez-Fernández; Eider Goñi; Arantza Fernández-Zabala (European Journal of Psychology Open)
Abstract: Introduction: Adolescence is a developmental stage during which adolescents often report lower levels of well-being. Understanding the factors that enhance subjective well-being is essential to its improvement. However, the specific relationships between emotional intelligence, resilience, and subjective well-being remain unclear. Aim: This study compares six theoretical models based on preliminary research exploring the relationship dynamics among emotional intelligence, resilience, and subjective well-being. Methods: Participants included 1,397 schoolchildren aged 12 to 16 years (M = 13.88; SD = 1.27). Results: The findings support a sequential model in which emotional intelligence directly predicts both positive (emotional clarity and repair) and negative (emotional attention and clarity) effects. Emotional intelligence also indirectly influences these variables through resilience, while resilience directly and indirectly predicts life satisfaction via the affective domain. Discussion: The results reveal a stepwise relationship dynamic, highlighting the mediational role of resilience and affective balance. Additionally, the affective components of subjective well-being play distinct roles compared to life satisfaction when analyzed alongside other well-being-related variables in a multivariate framework. This study opens up new avenues for enhancing adolescent life satisfaction.